Occurrence and isotype of antibodies against peripheral nerve myelin in serum from patients with peripheral neuropathy and healthy controls. Issue 6 (June 1988) - Cruz, M; Ernerudh, J; Olsson, T; Höjeberg, B; Link, H
Abstract : Antibodies against peripheral nerve myelin have previously been demonstrated in serum from patients with peripheral neuropathy and IgM paraproteinaemia, and a causal relationship has been suggested. Using enzyme-linked immunosorbent assay (ELISA), anti-myelin antibodies were found in sera from eight of 16 patients with polyneuropathy and paraproteinaemia, but also in 17% of 109 patients with peripheral neuropathy lacking monoclonal immunoglobulin, including five of 10 patients with Charcot-Marie-Tooth disease, and in 16% of 142 blood donors. The antibodies were mostly of IgM class in the two neuropathy groups, while blood donors had mostly IgA antibodies, and a few subjects of each group had antimyelin antibodies of two different isotypes. Western blot confirmed the ELISA results in a majority of antibody positive sera and revealed a 25-30 kD myelin target antigen for sera from the three groups, and for some of the non-paraproteinaemic sera also a 100 kD myelin target antigen. Our results demonstrate that the presence of serum autoantibodies against peripheral nerve myelin does not necessarily indicate a pathological event.